Sex Discrepancies in the Protective Effect of Opioid Agonist Therapy on Incident Hepatitis C Infection. (28th February 2019) - Geddes, Louise; Iversen, Jenny; Wand, Handan; Esmaeili, Aryan; Tsui, Judith; Hellard, Margaret; Dore, Gregory; Grebely, Jason; Dietze, Paul; Bruneau, Julie; Prins, Maria; Morris, Megan D; et al.
Abstract: Background: While opioid agonist therapy (OAT) reduces the risk of hepatitis C virus (HCV) acquisition among people who inject drugs (PWID), protective effects may be attenuated in females. We used pooled data from an international collaboration of prospective cohorts to assess sex disparities in HCV incidence among PWID exposed to OAT. Methods: Independent predictors of HCV infection were identified using Cox regression models with random effects after accounting for the clustering effect of study sites. Unadjusted and adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) are presented in sex‐specific analyses. Results: Among 701 participants exposed to OAT, HCV incidence was 16.5/100 person-years of observation (PYO) (95% CI, 13.1–20.7) in females and 7.6/100 PYO (95% CI, 6.0–9.5) in males (female:male adjusted HR [aHR], 1.80 [95% CI, 1.37–2.22]; P < .001). Factors associated with HCV acquisition among females exposed to OAT included nonwhite race (aHR, 1.79 [95% CI, 1.25–2.56]; P = .001), unstable housing (aHR, 4.00 [95% CI, 3.62–4.41]; P < .001), daily or more frequent injection (aHR, 1.45 [95% CI, 1.01–2.08]; P = .042), and receptive syringe sharing (aHR, 1.43 [95% CI, 1.33–1.53]; P < .001). Conclusions: Female PWID exposed to OAT are twice as likely as their male counterparts to acquire HCV. While there is a need for better understanding of sex differences in immune function and opioid pharmacokinetic and pharmacodynamic parameters, structural and behavioral interventions that target women are required to bolster the efficacy of OAT in preventing HCV transmission. Abstract : Utilizing longitudinal data from 7 international cohorts to examine sex differences in the protective effect of opioid agonist treatment on incident hepatitis C virus among people who inject drugs, we found that females were twice as likely as males to acquire infection.